Pengembangan LKPD Berwawasan Karakter Toleransi Pada Mata Pelajaran Pendidikan Kewarganegaraan Sekolah Dasar - Salati Asmahasanah; Laila Syifa; Fahmi Irfani (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2021)
This study aims to produce a Student Worksheet (LKPD) product based on the character education of tolerance towards students in class V Elementary School, and to find out the effectiveness of LKPD on student learning outcomes in instilling tolerance character education. This research method uses R&D research which consists of 8 stages, namely (1) potential and problem stages, (2) data collection stages, (3), product design stages, (4) design validation stages, (5), design improvement stages, (6) the trial stage, (7) the product revision stage, (8) the limited product stage. This study produced a PKN Student Worksheet (LKPD) based on tolerance attitude character education with an assessment of 91.5 linguists with very valid criteria, material experts 87.1 with very valid criteria, 96 design experts very valid. The results of the teacher's response were 92.5 with very good criteria as the final product in development. Then the test results obtained a value of 90% with very effective criteria, and the response of students was 83.75 with a very interesting category, and the achievement value of the tolerance attitude indicator was 95.6 with very valid criteria. Keywords : LKPD, Character Education, PKN, Tolerance